Context and priorities for health systems strengthening for pain and disability in low- and middle-income countries: a secondary qualitative study and content analysis of health policies. Issue 2 (25th July 2022) - Briggs, Andrew M; Jordan, Joanne E; Sharma, Saurab; Young, James J; Chua, Jason; Foster, Helen E; Haq, Syed Atiqul; Huckel Schneider, Carmen; Jain, Anil; Joshipura, Manjul; Kalla, Asgar Ali; Kopansky-Giles, Deborah; et al.
Abstract: Musculoskeletal (MSK) health impairments contribute substantially to the pain and disability burden in low- and middle-income countries (LMICs), yet health systems strengthening (HSS) responses are nascent in these settings. We aimed to explore the contemporary context, framed as challenges and opportunities, for improving population-level prevention and management of MSK health in LMICs using secondary qualitative data from a previous study exploring HSS priorities for MSK health globally and (2) to contextualize these findings through a primary analysis of health policies for integrated management of non-communicable diseases (NCDs) in select LMICs. Part 1: 12 transcripts of interviews with LMIC-based key informants (KIs) were inductively analysed. Part 2: systematic content analysis of health policies for integrated care of NCDs where KIs were resident (Argentina, Bangladesh, Brazil, Ethiopia, India, Kenya, Malaysia, Philippines and South Africa). A thematic framework of LMIC-relevant challenges and opportunities was empirically derived and organized around five meta-themes: (1) MSK health is a low priority; (2) social determinants adversely affect MSK health; (3) healthcare system issues de-prioritize MSK health; (4) economic constraints restrict system capacity to direct and mobilize resources to MSK health; and (5) build research capacity. Twelve policy documents were included, describing explicit foci on cardiovascular disease (100%), diabetes (100%), respiratory conditions (100%) and cancer (89%); none explicitly focused on MSK health. Policy strategies were coded into three categories: (1) general principles for people-centred NCD care, (2) service delivery and (3) system strengthening. Four policies described strategies to address MSK health in some way, mostly related to injury care. Priorities and opportunities for HSS for MSK health identified by KIs aligned with broader strategies targeting NCDs identified in the policies. MSK health is not currently prioritized in NCD health policies among selected LMICs. However, opportunities to address the MSK-attributed disability burden exist through integrating MSK-specific HSS initiatives with initiatives targeting NCDs generally and injury and trauma care.